Severe endothelial dysfunction in the aorta of a mouse model of Fabry disease; partial prevention by N-butyldeoxynojirimycin treatment. - Heare, T; Alp, N; Priestman, D; Kulkarni, AB; Qasba, P; Butters, T; Dwek, R; Clarke, K; Channon, K; Platt, F (2007)
OBJECTIVE: Fabry disease results from alpha-gala-ctosidase A deficiency and is characterized by the lysosomal accumulation of globotriaosylceramide. Globotriaosylceramide storage predominantly affects endothelial cells, altering vascular wall morphology and vasomotor function. Our objective was to investigate aortic globotriaosylceramide levels, morphology and function in a mouse model of Fabry disease, and the effect of substrate reduction therapy, using the glycosphingolipid biosynthesis inhibitor N-butyldeoxynojirimycin. METHODS AND RESULTS: Mice used were C57BL/6J and alpha-galactosidase A knockout (Fabry). We show progressive accumulation of aortic globotriaosylceramide throughout the lifespan of untreated Fabry mice (55-fold elevation at 2 months increasing to 187-fold by 19 months), localized to endothelial and vascular smooth-muscle cells; there was no effect on vascular wall morphology in young Fabry mice. In old mice, storage resulted in intimal thickening. Endothelial function declined with age in Fabry mouse aorta. Aortae from N-butyldeoxynojirimycin-treated Fabry mice at 19 months of age had reduced endothelial globotriaosylceramide storage, fewer morphological abnormalities and less severe vasomotor dysfunction compared with untreated littermates. CONCLUSION: We provide evidence of a novel vascular phenotype in the Fabry mouse that has relevance to vascular disease in Fabry patients. N-Butyldeoxynojirimycin treatment partially prevented the phenotype in the Fabry mouse by reducing endothelial globotriaosylceramide storage.